Complete chloroplast genome sequence of an alpine rhubarb Rheum likiangense - Liu, Mingyu (Mitochondrial DNA B Resour, 2020)
Rheum likiangense Samuelsson (Polygonaceae) is an endangered alpine rhubarb in the Qinghai-Tibet Plateau. In this study we report the complete chloroplast genome sequence (plastome) of Rh. likiangense. The assembled plastome is 162,291 bp in length with 31,741 bp inverted repeat (IR) regions and 128 annotated genes, including 34 tRNA genes, 8 rRNA genes, and 86 protein-coding genes. Phylogenetic analyses based on the full plastome sequences suggest the close relationship of Rh. likiangense with Rh. acuminatum and Rh. nobile. The plastome reported here is highly useful for designing plastome SSR markers to conduct a further conservation genetic study of this endangered rhubarb.